2021
DOI: 10.1093/brain/awab061
|View full text |Cite
|
Sign up to set email alerts
|

Ageing promotes pathological alpha-synuclein propagation and autonomic dysfunction in wild-type rats

Abstract: Neuronal aggregates of misfolded alpha-synuclein protein are found in the brain and periphery of patients with Parkinson’s disease. Braak and colleagues have hypothesized that the initial formation of misfolded alpha-synuclein may start in the gut, and then spread to the brain via peripheral autonomic nerves hereby affecting several organs, including the heart and intestine. Age is considered the greatest risk factor for Parkinson’s disease, but the effect of age on the formation of pathology and its propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 66 publications
8
70
1
Order By: Relevance
“…Mechanistically, it has been proposed that the initial formation of misfolded α-Syn occurs in the gut and then spreads to the brain via peripheral autonomic nerves, thus affecting several other organs, including the heart and intestine [ 153 ]. A recent study by the Van Den Berge group, using rats as an experimental model system, demonstrated marked age-dependent gut-to-brain and brain-to-gut spreading of α-Syn pathology along the sympathetic and parasympathetic nerves, and age-dependent dysfunction of the heart and stomach, as in patients with Parkinson’s disease [ 154 ]. Accordingly, it has been reported that trans-neuronal propagation of α-Syn pathology leads to sensory neuron dysfunction and neuropathic impairment, suggesting one of the pathogenic mechanisms underlying PD [ 155 ].…”
Section: Hiapp In Neurodegenerative and Metabolic Diseases: A Possibl...mentioning
confidence: 99%
“…Mechanistically, it has been proposed that the initial formation of misfolded α-Syn occurs in the gut and then spreads to the brain via peripheral autonomic nerves, thus affecting several other organs, including the heart and intestine [ 153 ]. A recent study by the Van Den Berge group, using rats as an experimental model system, demonstrated marked age-dependent gut-to-brain and brain-to-gut spreading of α-Syn pathology along the sympathetic and parasympathetic nerves, and age-dependent dysfunction of the heart and stomach, as in patients with Parkinson’s disease [ 154 ]. Accordingly, it has been reported that trans-neuronal propagation of α-Syn pathology leads to sensory neuron dysfunction and neuropathic impairment, suggesting one of the pathogenic mechanisms underlying PD [ 155 ].…”
Section: Hiapp In Neurodegenerative and Metabolic Diseases: A Possibl...mentioning
confidence: 99%
“…Despite the considerable understanding of PD symptoms, the exact pathogenesis of AutD is still largely unknown. Studies that demonstrate neuronal loss and abnormal aggregation of α-synuclein in the autonomic nervous system, including the dorsal motor nucleus of the vagus and sympathetic ganglia, may provide a pathological explanation for PD ( Gelpi et al, 2014 ; Van Den Berge et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonmotor symptoms including constipation caused by gastrointestinal legions in PD precede motor symptoms by 10-20 years. Therefore, it is hypothesized that α-synuclein fibrils in PD pathology are formed initially in the ENS or sensory nervous system, before spreading in a prion-like fashion from the ENS to the CNS, in part via the vagal nerve [66][67][68][69][70]. Furthermore, bidirectional gut-to-brain and brain-to-gut transmission patterns of α-synuclein have been proposed, and the former pattern depends on gut environmental factors including the microbiota, which elicit mucosal inflammation, oxidative stress, and protein accumulation [71][72][73][74][75].…”
Section: Gsh Prevents Da Quinone-induced Neurotoxicitymentioning
confidence: 99%